Fractures of the Scapula in Dogs: A Retrospective Review of 12 Cases - Harari, J.; Dunning, Dianne (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The case records of 12 dogs with scapular fractures were reviewed; feline patients were not identified. Fractures of the scapula were treated in approximately 2.4% of the total patients with fractures. Eleven of twelve dogs sustained a scapular fracture, following vehicular trauma. The most frequent type of fracture involved the body or spine of the scapula. Open surgical repair, or conservative non-surgical therapy, yielded successful clinical outcome by three months, in most of the cases. In 60% of the patients, concurrent thoracic injuries were reported, although complications were rare.Twelve dogs with scapular fractures were, treated surgically or by non-operative therapy. Although concurrent thoracic cavity lesions were frequent, successful clinical outcome was achieved, in most cases, by three months following injury.
Keywords: Scapula; fracture; dog